“Keep Portland Weird”? Carnivalesque Elements in the Rebranding of the Portland Book Festival - Noorda, Rachel; Berens, Kathi (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2020)
The Portland Book Festival, originally known as “Wordstock,” is the main annual literary event in Portland, Oregon. It is also an increasingly prominent literary festival in the United States. The branding shift from “Wordstock” to “Portland Book Festival” in 2018 unearths key tensions, hierarchies, subversions, and cultural changes in the communicative and social functions of the Festival. The essay identifies transactional and transformative aspects of the Festival. Bank of America’s festival-naming “title” sponsorship, the partnership of cultural heritage organizations, and Portland place branding offer transactional stability for the Festival, where parties give and get in kind. The Festival’s temporary affective bonds and their social media documentation facilitate transformational experiences that reinscribe hierarchies of centre/periphery. The name change fosters a more democratic and accessible festival experience. This article takes a multimethod approach, triangulating sentiment analysis of tweets from the 2017 and 2018 Festivals, a survey of 2018 Portland Book Festival attendees, and interviews with prominent stakeholders in the Festival rebranding.